Expression and antiviral application of exogenous lectin (griffithsin) in sweetpotatoes - Liu, Shuai; Yu, Yang; Guo, Ke; Zhang, Qian; Jia, Zhaodong; Alfredo, Morales Rodriguez; Ma, Peiyong; Xie, Hao; Bian, Xiaofeng (Frontiers in Plant Science, 2024)
Griffithsin (GRFT) is a highly effective, broad-spectrum, safe, and stable viral inhibitor used to suppress a variety of viruses. However, little information is available on whether GRFT can prevent plant viral diseases. In this study, we constructed a GRFT overexpression vector containing the sweetpotato storage cell signal peptide and generated exogenous GRFT overexpression lines through genetic transformation. The transgenic plants showed notable resistance to sweetpotato virus disease in the virus nursery. To verify the anti-plant virus function of GRFT, transient expression in tobacco leaves showed that GRFT inhibited the sweetpotato leaf curl virus (SPLCV). The replication of SPLCV was entirely inhibited when the concentration of GRFT reached a certain level. The results of pulldown and BIFC assays showed that GRFT did not interact with the six components of SPLCV. In addition, the mutated GRFT D/A without the binding ability of carbohydrate and anti-coronavirus function, in which three aspartate residues at carbohydrate binding sites were all mutated to alanine, also inhibited SPLCV. Quantitative reverse-transcription PCR analyses showed that the tobacco antiviral-related genes HIN1, ICS1, WRKY40, and PR10 were overexpressed after GRFT/GRFT D/A injection. Furthermore, HIN1, ICS1, and PR10 were more highly expressed in the leaves injected with GRFT D/A . The results suggest that sweetpotato is able to express GRFT exogenously as a bioreactor. Moreover, exogenous GRFT expression inhibits plant viruses by promoting the expression of plant antiviral genes.